The Effect of Training and Leadership on Aviation Security (AVSEC) Personnel Performance at Halim Perdanakusuma Airport Jakarta - Dahruin, Dahruin (Dinasti International Journal of Management Science, 2025)
This study aims to determine whether there is an influence of Training, Leadership, and Work Discipline on the Performance of Aviation Security (AVSEC) personnel at Halim Perdana Kusuma Airport, Jakarta. The method used in this study is a quantitative method. The sample in this study amounted to 25 people. The data collection technique was by distributing questionnaires and processed using the SPSS version 24 application. This study uses multiple linear regression analysis, and hypothesis testing using the t test and F test. The results of the study showed that in the partial test (t) the training variable had an effect on employee performance, the leadership variable had no effect on employee performance, the work discipline variable had an effect on employee performance. The results of the simultaneous test (F) the training, leadership, and work discipline variables had an effect on employee performance by 74%.